The Speciality of Language and Folk Crafts in the Turkic World (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the specific aspects of language and folk crafts in the Turkic world. From the point of view of lexical, grammatical and stylistic composition, social specificity and the linguistic personality can process socio-cultural information depending on their gender and social status, and folk crafts can only be passed down from generation to generation in a worthy way, regardless of the period, and it pays special attention to issues such as stepping into a new era without losing nationality and culture. Since the first year of the 21st century, there has been an increasing effort to appeal to folk art, its priceless spiritual heritage, and to develop it, bringing it to a level where countries around the world, especially in the Turkic Commonwealth, can compete with their crafts in other fields. We can see this in various exhibitions, exhibitions dedicated to folk crafts and textiles, light industry, especially in the world of fashion and design, where atlas, unique examples of our addresses occupy a special place in the exhibition hall.